Children's acquisition of negation in L1 Afrikaans. Issue 1 (February 2023) - White, Michelle Jennifer; Southwood, Frenette; Huddlestone, Kate
Afrikaans is a West Germanic language that originated in South Africa as a descendent of Dutch. It displays discontinuous sentential negation (SN), where negation is expressed by two phonologically identical negative particles that appear in two different positions in the sentence. The negation system is argued to be an innovation that came about through the reanalysis of a discourse-dependent (pragmatically conditioned) structure in Dutch, reinforced by proponents of the standardisation of Afrikaans who prescriptively imposed a negative concord structure onto the Dutch negation system. The Afrikaans negation system is therefore argued to be artificially created, making it crosslinguistically rare and syntactically complex, the latter possibly having a delaying effect on acquisition. This study investigates both the comprehension and production of negation by young child speakers of Afrikaans. Sentences containing negative indefinites (NIs) ( niks 'nothing' and geen 'no'/ 'none' with a final negative particle) are compared with those containing two negative particles (referred to as SN), which are syntactically less complex. We examined (1) whether the comprehension of sentences with NIs is more difficult to acquire than that of sentences using SN and (2) when and how negation is produced by young children. Data were collected through a picture selection task (comprehension) and recordings of spontaneous speech during free play (production). Results show that the comprehension of SN was acquired before that of NI, indicating that sentences containing NIs were indeed more difficult to comprehend than those containing SN. The production data showed that even the youngest participants (age 3;0) could produce grammatically well-formed negated constructions, but that errors occurred until age 4;3. In comparison with that found for other West Germanic languages, Afrikaans' complex system of expressing negation seems to have a delaying effect on the comprehension of negation, specifically NIs, but not on production.